Decision taking in corneal refractive surgery. Issue 3 (March 2023) - Nuijts, Rudy M.M.A.; Cummings, Arthur B.; Dick, H. Burkhard; Taneri, Suphi; Vinciguerra, Paolo; Cochener-Lamard, Béatrice; Lapid-Gortzak, Ruth; Kanellopoulos, A. John; Agarwal, Kanika; Karadimou, Despoina; Konstantinidou, Elena; Shetty, Rohit; et al.
Abstract : A 27-year-old woman wants to get rid of contact lenses and spectacles. She had strabismus surgery as a child and now shows mild nondisturbing exophoria. Abstract : A 27-year-old woman who wants to get rid of contact lenses and spectacles was seen at our clinic. She had strabismus surgery as a child and was patched for the right eye but now shows mild nondisturbing exophoria. Infrequently, she likes to box in the sports school. Her corrected distance visual acuity at presentation in the right eye was 20/16 with −3.75 −0.75 × 50 and in the left eye 20/16 with −3.75 −1.25 × 142. Her cycloplegic refraction in the right eye was −3.75 −0.75 × 44 and in the left eye was −3.25 −1.25 × 147. The left eye is the dominant eye. The tear break-up time was 8 seconds in both eyes, and the Schirmer tear test was 7 to 10 mm in right and left eyes, respectively. Pupil sizes under mesopic conditions were 6.62 mm and 6.68 mm. The anterior chamber depth (ACD) (measured from the epithelium) in the right eye was 3.89 mm and in the left eye was 3.87 mm. The corneal thickness was 503 μm and 493 μm of the right and left eye, respectively. Corneal endothelial cell density was on average 2700 cells/mm 2 for both eyes. Slitlamp biomicroscopy showed clear corneas and a normal flat iris configuration. Supplemental Figures 1 to 4 (available at http://links.lww.com/JRS/A818, http://links.lww.com/JRS/A819, http://links.lww.com/JRS/A820, and http://links.lww.com/JRS/A821 ) show the corneal topography and Belin-Ambrósio deviation (BAD) maps at presentation of the right eye and left eye, respectively. Would you consider this patient a candidate for corneal refractive surgery (eg, laser-assisted subepithelial keratectomy, laser in situ keratomileusis [LASIK], or small-incision lenticule extraction [SMILE] procedure)? Has your opinion changed given the recent opinion of the U.S. Food and Drug Administration (FDA) regarding LASIK? 1 The patient herself is slightly favoring an implantation of a phakic intraocular lens (pIOL), as she prefers something reversible. Would you implant a pIOL, and which type of IOL, for this level of myopia? What is your diagnosis or are additional diagnostic methodologies needed to establish a diagnosis? What is your treatment advice for this patient? REFERENCES 1. U.S. Food and Drug Administration, HHS. Laser-assisted in situ keratomileusis (LASIK) lasers–patient labeling recommendations; draft guidance for industry and food and drug administration staff; availability. July 28, 2022, Federal Register; 87 FR 45334. Available at: https://www.fda.gov/regulatory-information/search-fda-guidance-documents/laser-assisted-situ-keratomileusis-lasik-lasers-patient-labeling-recommendations Accessed January 25, 2023